An Evaluation of the Vocational Readiness Package for Girls: A Solution to One Problem - Leith, Nancy; Fitzsimmons, George (Canadian Journal of Counselling and Psychotherapy, 2012)
In this study the effectiveness of the Canadian Vocational Readiness Package for Girls was investigated. It was hypothesized that exposure to this program would significantly increase the vocational awareness level of highschool girls. It was also predicted that participation in this program would stimulate highschool girls to investigate their individual career plans with a counsellor. The data from this study supported both hypotheses. The Vocational Readiness Package for Girls appeared to be an excellent program for meeting the special vocational counselling needs of today's female adolescent.